Optimalisasi Peran Keluarga dalam Membangun Kebiasaan Membaca Anak melalui Pendampingan Penyusunan Jadwal Membaca Harian - Hilmiyatun H; Lalu Nova Saza Yusma (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
The low reading habits of children within the family environment indicate the need to strengthen literacy culture through active parental involvement. This community service program aimed to improve children's reading habits through a family-based literacy assistance program by developing a daily reading schedule. The program was implemented in Orong Tengak Hamlet, Pelambik Village, Southwest Praya District, Central Lombok Regency, involving 10 elementary school children and their 10 parents. The method employed was participatory mentoring, consisting of the stages of observation, literacy education, development and implementation of a daily reading schedule, and monitoring and evaluation. Data were collected through observation, interviews, documentation, and mentoring records, and were analyzed using descriptive qualitative methods. The results showed that the program increased parents' involvement in supporting their children's reading activities, helped establish more consistent reading habits among children, and encouraged the productive use of leisure time through educational activities. Therefore, family-based literacy assistance through the implementation of a daily reading schedule can serve as an effective alternative for strengthening literacy culture within the family environment.